Efficacy and safety of advanced hybrid closed loop systems in children with type 1 diabetes younger than 6 years - Rapini, Novella; Martino, Mariangela; Arnaldi, Claudia; Deodati, Annalisa; Anagnostopoulou, Lilian; Amodeo, Maria Elisa; Ciampalini, Paolo; Pampanini, Valentina; Lorubbio, Antonella; Tosini, Davide; Cianfarani, Stefano; Schiaffini, Riccardo (Frontiers in Endocrinology, 2024)
Background: Tight glycemic control is essential for normal growth and development in preschool children. The aim of our study was to evaluate the impact of Advanced Hybrid Closed Loop (AHCL) systems in a real-life setting in children younger than 6 years. Methods: We conducted a two centre prospective study. We enrolled 19 patients with a median age at the disease onset of 2.6 years (IQR 1.6; 4.4) and a median disease duration of 1.4 years (IQR 0.9; 2.8) who were switched to AHCL from multiple daily injections or open loop insulin therapy and with a 6 months follow-up. Clinical data, sensor glycemic metrics and pump settings were collected and analyzed. Results: After 6 months of follow-up there was a significant reduction of median HbA1c (p=0.0007) and glucose management indicator (p=0.03). A reduction both in mild (>180 mg/dl) (p=0.04) and severe (>250 mg/dl) (p=0.01) hyperglycemia was observed after 1 month of automode and in mild hyperglycemia persisted up to 6 months (p=0.02). A small increase in time below range (<70 mg/dl) was observed (p=0.04) without significant difference in time <54 mg/dl (p=0.73). Time in Range increased significantly, reaching a 10% increment (p=0.03) compared with baseline. A significant reduction in the average sensor glucose was observed (p=0.01) while coefficient of glucose variability (CV%) remained stable (p=0.12). No episodes of ketoacidosis or severe hypoglycemia have been recorded. Conclusion: AHCL systems are effective and safe for children younger than 6 years and should be considered as a valid therapeutic option from diabetes onset.